Cubital Tunnel Decompression: Equivalent Outcome Scores when Procedure Performed with Local versus General Anesthetic - Ajwani, S. H.; Unsworth, R. M.; Tseng, M.; Madi, M.; Berg, A.; Warner, J. G.; Wykes, P. R. (Journal of Hand and Microsurgery, 2019)
Background Ulnar nerve compression at the cubital tunnel is the second commonest upper limb neuropathy. Unlike carpal tunnel surgery, most of decompression procedures for this condition are undertaken using general anesthesia (GA). This has inherent economic and patient safety implications. We aimed to assess if there is a difference in early and medium-term outcome scores in patients who have cubital tunnel decompression under general versus local anesthesia (LA).Materials and Methods We undertook a patient outcome evaluation of patients who were under the care of two upper limb surgeons. Patients were evaluated postoperatively using the patient-related ulnar nerve evaluation (PRUNE) questionnaire. Patients were contacted by phone, mail, and face to face in clinics.Results A total of 34 patients were identified in the study. Eleven were excluded from the study. Thirteen patients underwent surgery under LA. The LA group had their procedures performed using local infiltration of the surgical site with 20 mL of 0.5% bupivacaine with adrenaline. Ten patients had their procedures using standard GA and tourniquet. The average PRUNE score in the LA group was 33.8, and that in the GA group was 34.1. This difference in PRUNE score was not statistically significant p > 0.05.Discussion Our data suggest that there is no significant difference in early and midterm outcomes between patients who undergo cubital tunnel decompression using either GA or LA. We advocate the use of LA as it does lead to decreased anesthetic risk and has obvious economic benefits such as lowering the demands on theater and anesthetic resources.
Keywords: local anesthesia; cubital tunnel decompression; outcomes